(untitled) (Baltic Journal of Sport and Health Sciences, 2014)
Background. Lately scientists abroad and in Lithuania have been interested in the peculiarities of motor learning and control. As the recent research shows, psychomotor parameters of persons with disabilities receive much attention from the community. However, we could find only a few scientific papers dealing with the psychomotor peculiarities of the disabled people, deaf people among. Research aim was to evaluate psychomotor reactions and hemodynamic indices of persons with hearing impairments, athletes and male persons who did not go in for sports. Methods. Twenty two young persons with hearing impairments took part in the study. Among them there were deaf players from the national basketball team (age 23.80 ± 2.6 years), (45.5%, n = 10). Persons with hearing impairments who did not go in for sports were in the control group (age 21.75 ± 1.8 years), (54.5%, n = 12). Research was carried out in the Lithuanian Sports University (LSU) using the analyser of dynamic parameters DPA – 1 for human hand and leg movements in the laboratory of motor control. Results. Simple and complex reaction time was statistically different only after physical exercise between athletes with hearing impairments and those who did not go in for sports (p < 0.05). Simple psychomotor reaction time of athletes with inborn and acquired hearing impairments before and after exercise was not statistically significantly different. There were no significant changes in simple and complex reaction time and hemodynamic parameters (double product) of athletes with inborn hearing impairment after the 6-minute walking test. Conclusion. Simple and complex reaction time in athletes with hearing impairment and those who did not go in for sports was statistically different (p < .05) only after physical strain in sportsmen. Having tested simple psychomotor time reaction in deaf persons since birth and those with the acquired hearing impairment before and after exercise we found that there was no significant difference ( p > .05) between them, but the complex reaction time in subjects with acquired hearing impairment before and after exercise was shorter than in persons who were deaf since birth. However, the difference was also not significant (p > .05). There were also no significant changes in simple and complex reaction time and hemodynamic parameters (double product) in athletes who were deaf since birth after the 6 min walking test. Keywords: hearing impairment, psychomotor parameters, reaction time.